Exploration of Multi Meeting, Multitasking and Meeting Fatigue to Productivity - Maharani, Anita; Marlika, Selvia; Triyanti, Triyanti; Pandu, Thenry Linda Sharron (Emerging Markets : Business and Management Studies Journal, 2021)
This study aimed to see the effect of multi-meeting, multitasking, and meeting fatigue on productivity. The context of this study is during the Covid-19 pandemic, where phenomena related to multi-meeting, multitasking, and meeting fatigue were entirely natural. The literature used is related to multi-meeting, multitasking, and meeting fatigue, as well as productivity. We elaborate on several pieces of literature before the pandemic, and this study emerges from the results of studies during the pandemic. This research method refers to a quantitative approach, which wants to see the relationship between variables; SMART PLS a test tool. The researcher conducts a reliability test by looking at CR and AVE, a validity test by looking at discriminant validity, and finally, conducting a path analysis by looking at the results of P-Values. This study indicates that meeting fatigue does not negatively affect productivity; multitasking has a positive effect on productivity, meeting fatigue can affect productivity when there are multi meetings as moderators, and multitasking affects productivity when there are multi meetings as moderators.